Bone marrow coagulated and low‐level laser therapy accelerate bone healing by enhancing angiogenesis, cell proliferation, osteoblast differentiation, and mineralization. Issue 6 (20th August 2020) - Santinoni, Carolina S.; Neves, Adrieli P. C.; Almeida, Breno F. M.; Kajimoto, Natália C.; Pola, Natália M.; Caliente, Eliana A.; Belem, Eduarda L. G.; Lelis, Joilson B.; Fucini, Stephen E.; Messora, Michel R.; Garcia, Valdir G.; Bomfim, Suely R. M.; et al.
Abstract: The present study evaluated bone marrow aspirate (BMA) and low‐level laser therapy (LLLT) on bone healing. It was created critical‐size defects (CSD) of 5 mm diameter in rat calvaria of 64 rats. Animals were randomly divided into four groups: Control (blood clot), BMA (coagulated BMA), LLLT (laser irradiation and blood clot), and BMA/LLLT (laser irradiation and coagulated BMA). Euthanasia was performed at 15 or 30 days postoperative. Immunohistochemical reactions were performed to identify vascular endothelial growth factor (VEGF), proliferating cell nuclear antigen (PCNA), runt‐related transcription factor‐2 (Runx2), bone morphogenetic protein‐2 (BMP‐2), osteocalcin (OCN), and osteopontin (OPN). The markers were quantified, and data were statistically analyzed. Groups BMA/LLLT and LLLT presented significantly higher VEGF expression than group control. Group BMA/LLLT presented a significantly higher expression of PCNA than all experimental groups. Groups BMA and BMA/LLLT presented significantly higher expression of BMP‐2 than all experimental groups. Groups LLLT and BMA/LLLT presented significantly higher expression of OPN than groups control and BMA. Groups LLLT, BMA, and BMA/LLLT presented a significantly higher expression of OCN than group control. It can be concluded that the association of BMA and LLLT enhanced bone healing by improving expression of VEGF, PCNA, Runx2, BMP‐2, OPN, and OCN.